Antenna-in-Package and transmit–receive switch for single-chip radio transceivers of differential architecture - Zhang, Yue Ping (2010)
A fully differential architecture from the antenna to the integrated circuit is proposed for radio transceivers in this paper. The physical implementation of the architecture into truly single-chip radio transceivers is described for the first time. Two key building blocks, the differential antenna and the differential transmit-receive (T-R) switch, were designed, fabricated, and tested. The differential antenna implemented in a package in low-temperature cofired-ceramic technology achieved impedance bandwidth of 2%, radiation efficiency of 84%, and gain of 3.2 dBi at 5.425 GHz in a size of 15 x 15 x 1.6 mm3. The differential T-R switch in a standard complementary metal-oxide-semiconductor technology achieved 1.8-dB insertion loss, 15-dB isolation, and 15-dBm 1-dB power compression point (P 1dB) without using additional techniques to enhance the linearity at 5.425 GHz in a die area of 60 x 40 µm2.